Model for implementation of teleworking in software development organizations (2017)
This paper provides a consultation tool for implementation of teleworking in software development or ganizations. This concept was born for using highly experienced human talent with specific knowledge and skills, in activities that contribute to the development of technological projects within organizations dedicated to development of software, without its physical presence being necessary, as is the case of the Center for Applied Research in Development and Information Technologies [CIADTI] of the Universidad de Pamplona (Colombia). A model that results from the investigation is exposed, which was applied and validated, with an acceptance higher than 79%, so its implementation can be considered in other organizations.